Virulence of Listeria monocytogenes isolated from the cheese dairy environment, other foods and clinical cases - Neves, Elsa (2013)
The virulence potential of 51 Listeria monocytogenes isolates, including strains from cheese, cheese production environments and from human cases of listeriosis, was evaluated in this study. The isolates were used to infect HT-29 cell monolayers in an in vitro test of virulence, based on a plaque-forming assay (PFA). Fifteen selected isolates were used for subcutaneous footpad inoculation in mice and subsequent recovery of the bacterium from the spleen 3 days after inoculation. In the PFA, two isolates from milk (serovar 1/2a) were not significantly different (P,0.05) from the low-virulence strain (442) used as reference. Thirty-three isolates were not significantly different (P,0.05) from the virulent strain (EGDe) used as reference. Nine isolates were significantly more virulent (highly virulent) than the EGDe strain and seven isolates were significantly less virulent. The nine highly virulent isolates were either from humans (four), from cheese dairy environments (two isolates of a strain were found persistently in two dairies), from cheese (one), from milk (one) and the reference strain for serovar 1/2b (CECT 936). The two milk isolates with low virulence in the PFA were found to be virulent in mice. In conclusion, all the isolates from food and food-related environments were potentially virulent or highly virulent. These results stress the risk of listeriosis associated with the consumption of cheese contaminated with L. monocytogenes, and once more emphasize the importance of good manufacturing practices (GMPs) together with sanitation standard operating procedures (SSOPs) throughout the food chain.